Grace notes - Allen Charlotte Vale 1941 (Don Mills, Ont. : MIRA, 2002)
Early in her marriage, Grace Loring became the victim of her husband's unpredictable rages. Taking her infant daughter, Grace fled to the safety of her brother Gus's home in Vermont. Now, Grace is a successful author with her own web site. Accustomed to abused women writing to ask for advice, Grace is contacted by a troubled young woman named Stephanie Baine. When Stephanie's e-mails abruptly stop, Grace fears the worst. Then the e-mails resume, and Grace learns that everything she believed about Stephanie may not be true.
Keywords: Authors American -- Fiction; Wife abuse -- Fiction; Family violence -- Fiction; Web sites -- Fiction; Vermont -- Fiction; Suspense fiction